A graphene-sandwiched DNA nano-system: regulation of intercalated doxorubicin for cellular localization. Issue 12 (3rd November 2020) - Nandi, Semonti; Kale, Narendra; Patil, Ashwini; Banerjee, Shashwat; Patil, Yuvraj; Khandare, Jayant
Abstract : Regulation and control over the cellular localization employing graphene oxide (GO) and iron oxide (Fe3 O4 ) NPs and sandwiched deoxyribonucleic acid (DNA) intercalated with anticancer drug doxorubicin (DOX). Abstract : Control of the sub-cellular localization of nanoparticles (NPs) with enhanced drug-loading capacity, employing graphene oxide (GO), iron oxide (Fe3 O4 ) NPs and sandwiched deoxyribonucleic acid (DNA) bearing intercalated anticancer drug doxorubicin (DOX) has been investigated in this work. The nanosystems G–DNA–DOX–Fe3 O4 and Fe3 O4 –DNA–DOX differentially influence serum protein binding and deliver DOX to lysosomal compartments of cervical cancer (HeLa) cells with enhanced retention. Stern–Volmer plots describing BSA adsorption on the nanosystems demonstrated the quenching constants, K sv for G–DNA–DOX–Fe3 O4 and Fe3 O4 –DNA–DOX (0.025 mL μg −1 and 0.0103 mL μg −1 respectively). Nuclear DOX intensity, measured at 24 h, was ∼2.0 fold higher for Fe3 O4 –DNA–DOX in HeLa cells. Parallelly, the cytosol displayed ∼2.2 fold higher DOX intensity for Fe3 O4 –DNA–DOX compared to G–DNA–DOX–Fe3 O4 . Fe3 O4 –DNA–DOX was more efficacious in the cytotoxic effect than G–DNA–DOX–Fe3 O4 (viability of treated cells: 33% and 49% respectively). The DNA:nanosystems demonstrated superior cytotoxicity compared to mole-equivalent free DOX administration. The results implicate DNA:DOX NPs in influencing the cellular uptake mechanism and were critically subject to cellular localization. Furthermore, cell morphology analysis evidenced maximum deformation attributed to free-DOX with 34% increased cell roundness, 63% decreased cell area and ∼1.9 times increased nuclear-to-cytoplasmic (N/C) ratio after 24 h. In the case of Fe3 O4 –DNA–DOX, the N/C ratio increased 1.2 times and a maximum ∼37% decrease in NSA was noted suggesting involvement of non-canonical cytotoxic pathways. In conclusion, the study makes a case for designing nanosystems with controlled and regulated sub-cellular localization to potentially exploit secondary cytotoxic pathways, in addition to optimized drug-loading for enhanced anticancer efficacy and reduced adverse effects.